(untitled) (Universal International Scientific Journal, 2026)
The article highlights the importance of modern approaches and techniques in the development of cognitive independence of students. Intensification of informatization processes, providing students with educational materials through colorful pictures and graphics, helps to increase motivation and develop cognitive independence. Educational reforms, while increasing the demand for qualified personnel and professionals, help to strengthen students ’ interest and motivation for classes. Through the creation of problem situations, creativity and discussion, the need to develop students ’ activity and independent thinking skills is emphasized. Cognitive independence, which involves independent activities and aspirations in the learning process, is also indicated to be developed through pedagogical techniques and approaches